الاعلام وأبعاده التنموية في المجتمع الجزائري في ظل تكنولوجيا الاتصال الحديثة - قدادرة, شوقي; بن خليفة, إسماعيل (جامعة الوادي - University of Eloued, 2021)
لا شك أن من أهم القضايا التي تشغل بال الكثيرين من صناع القرار على المستوى الاقتصادي و الاجتماعي والتنموي، قضية الإعلام ودوره في عملية التنمية، حيث تعد من أبرز المواضيع المطروحة على الساحة الدولية في الوقت الراهن وخاصة بعدما تبين الارتباط الوثيق بين الاعلام والتنمية لتحقيق آمال و تطلعات المجتمع في تنمية مستدامة وقد المح لذلك العالم " ويلبر شرام " في كتابه " الاعلام و التنمية " و تأتي هذه الورقة البحثية لتميط اللثام عن ملمح الاعلام التنموي و مرتكزاته النظرية و كذا تعمل على ابراز أهم سماته وخصائصه الكفيلة بتحقيق النجاح لتنمية مستدامة, كما تطرقت هذه الورقة البحثية الى تطور السياسة الاعلامية للتنمية في الجزائر كنموذج يمكن الوقوف على إيجابياته وسلبياته. Abstract : There is no doubt that one of the most important issues that concern many decision makers on the economic, social and developmental level is the issue of media and its role in the development process, as it is one of the most prominent issues on the international scene at the present time, especially after it was revealed the close link between media and development to achieve hopes and Society aspirations for sustainable development. That scholar, Wilbur Schramm, hinted in his book "Information and Development". This research paper comes to unveil the development media's hint and its theoretical foundations, as well as highlighting its most important features and characteristics capable of achieving success for sustainable development, as I touched upon. H Its research paper to the evolution of media development policy in Algeria as a model can stand on its own pros and cons.
مقال
Keywords: الاعلام التنموي - الخصائص النظرية- المهمات المطلوبة; Development media - theoretical characteristics - the required tasks